COVID-19 and Extracellular Vesicles: An Intriguing Interplay - Gabriella Pocsfalvi; Ramila Mammadova; Ana Paulina Ramos Juarez; Ramesh Bokka; Francesco Trepiccione; Giovambattista Capasso (Karger Publishers, 2020)
Background: The outbreak of severe acute respiratory syndrome β-coronavirus 2 (SARS-CoV-2) has the potential to become a long-lasting global health crisis. The number of people infected with the novel coronavirus has surpassed 22 million globally, resulting in over 700,000 deaths with more than 15 million people having recovered (https://covid19.who.int). Enormous efforts are underway for rapid vaccine and treatment developments. Amongst the many ways of tackling the novel coronavirus disease 2019 (COVID-19) pandemic, extracellular vesicles (EVs) are emerging. Summary: EVs are lipid bilayer-enclosed structures secreted from all types of cells, including those lining the respiratory tract. They have established roles in lung immunity and are involved in the pathogenesis of various lung diseases, including viral infection. In this review, we point out the roles and possible contribution of EVs in viral infections, as well as ongoing EV-based approaches for the treatment of COVID-19, including clinical trials. Key Messages: EVs share structural similarities to viruses and recent findings demonstrate that viruses exploit EVs for cellular exit and EVs exploit viral entry mechanisms for cargo delivery. Moreover, EV-virus interplay could be exploited for future antiviral drug and vaccine development. EV-based therapies, especially the mesenchymal stem cell-derived EVs, are being intensively studied for the treatment of COVID-19.